2023
DOI: 10.20945/2359-3997000000622
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of subclinical atherosclerosis in obese patients with three noninvasive methods: Arterial stiffness, carotid intima-media thickness, and biomarkers of endothelial dysfunction

Abstract: Objective: In this study, we aimed to evaluate subclinical atherosclerosis in patients with obesity who had cardiovascular disease risk indicators such as arterial stiffness, which is evaluated using pulse wave velocity (PWV), carotid intima-media thickness (CIMT), and biomarkers of endothelial dysfunction such as endocan, ADAMTS97, and ADAMTS9. Subjects and methods: Sixty obese subjects, including 23 subjects with body mass index (BMI) ≥ 40, 37 subjects with BMI ≥ 30 but < 40, and 60 age-and sex-matched contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…CIMT was measured according to the Mannheim protocol using a linear ultrasound transducer (3)(4)(5)(6)(7)(8)(9)(10)(11)(12) [15]. Patients were in a supine position with their neck in extension and the probe was in an antero-lateral position.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CIMT was measured according to the Mannheim protocol using a linear ultrasound transducer (3)(4)(5)(6)(7)(8)(9)(10)(11)(12) [15]. Patients were in a supine position with their neck in extension and the probe was in an antero-lateral position.…”
Section: Methodsmentioning
confidence: 99%
“…The current body of literature is still generally inconclusive, although one interesting study showed no difference in CIMT between men and women with obesity after adjustment for classic cardiovascular risk factors, while premenopausal status was protective; thus, more well-designed studies are needed [ 8 ]. Different methods can be utilized as indicators of the risk of cardiovascular diseases such as CIMT, pulse wave velocity (PWV) and biomarkers of endothelial dysfunction, but people with body mass index (BMI) grade III had significantly higher levels of PWV and CIMT than the control group [ 9 ]. The goal of our study was to determine the effect of obesity on CIMT in people with no previous myocardial infarction, stroke or transient ischemic attack (TIA), using diverse anthropometric parameters.…”
Section: Introductionmentioning
confidence: 99%